A follow-up study of the 1950-1965 graduates of the then Agusan Agricultural High School (Northern Mindanao National Agricultural College) - De la Cruz, Gracia (Alviola) 1921- (s.n.], 1972)
The purpose of the study is to find out the actual conditions of agricultural school graduates, specifically those of the then Agusan Agricultural High School (now Northern Mindanao Agricultural College) in Ampayon, Butuan City, and the factors that influence the choices of, and establishment in, their respective life occupations. The study reveals whether vocational agricultural education has been performing its role in the promotion and growth of the agricultural economy of the country through its graduates